The People's Representative Council's Right to Inquiry Against the Corruption Eradication Commission Institution in the Perspective of Constitutional Law in Indonesia (International Journal of Education and Literature, 2024)
This research discusses the House of Representatives' (DPR) Right to Inquiry against the Corruption Eradication Commission (KPK) in the context of constitutional law in Indonesia. The right to inquiry is one of the control instruments possessed by the DPR to monitor the performance of state institutions, including the Corruption Eradication Commission. However, the application of the right to inquiry against the Corruption Eradication Committee has given rise to a number of debates regarding its authority and limitations in the constitutional justice system. This research analyzes the constitutional and regulatory basis regarding the DPR's right to inquiry against the KPK, as well as its impact on the independence and effectiveness of the KPK in eradicating corruption. By considering a constitutional law perspective, this research also evaluates the political and legal implications of implementing the right to inquiry against the Corruption Eradication Commission in the context of the system of monitoring and eradicating corruption in Indonesia.